The association between the workload of general practitioners and patient experiences with care: results of a cross-sectional study in 33 countries - Willemijn L. A. Schäfer; Michael J. van den Berg; Peter P. Groenewegen (BMC, 2020)
Abstract Background The workload of general practitioners (GPs) and dissatisfaction with work have been increasing in various Western countries over the past decades. In this study, we evaluate the relation between the workload of GPs and patients' experiences with care. Methods We collected data through a cross-sectional survey among 7031 GPs and 67,873 patients in 33 countries. Dependent variables are the patient experiences on doctor-patient communication, accessibility, continuity, and comprehensiveness of care. Independent variables concern the workload measured as the GP-reported work hours per week, average consultation times, job satisfaction (an indicator of subjective workload), and the difference between the workload measures of every GP and the average in their own country. Finally, we evaluated interaction effects between workload measures and what patients find important in a country and the presence of a patient-list system. Relationships were determined through multilevel regression models. Results Patients of GPs who are happier with their work were found to experience better communication, continuity, access, and comprehensiveness. When GPs are more satisfied compared to others in their country, patients also experience better quality. When GPs work more hours per week, patients also experience better quality of care, but not in the area of accessibility. A longer consultation time, also when compared to the national average, is only related to more comprehensive care. There are no differences in the relationships between countries with and without a patient list system and in countries where patients find the different quality aspects more important. Conclusions Patients experience better care when their GP has more work hours, longer consultation times, and especially, a higher job satisfaction.